Cadmium exposure impairs pancreatic β-cell function and exaggerates diabetes by disrupting lipid metabolism. (April 2021) - Hong, Huihui; Xu, Yudong; Xu, Jia; Zhang, Jingjing; Xi, Yu; Pi, Huifeng; Yang, Lingling; Yu, Zhengping; Wu, Qingqian; Meng, Zhuoxian; Ruan, Wei-Shuyi; Ren, Yunzhao; et al.
Graphical abstract: Highlights: Cd exposure induces pancreatic β-cell dysfunction and promotes the development of diabetes. Cd exposure disrupts lipid metabolism and induces lipid accumulation in MIN6 cells. Cd exposure promotes inflammation by increasing the weight of inflammatory bioactive lipids. Abstract: Cadmium is known as an environmental pollutant that contributes to pancreatic damage and the pathogenesis of diabetes. However, less attention has been devoted to elucidating the mechanisms underlying Cd-induced pancreatic β-cell dysfunction and the role of Cd toxicity in the development of diabetes. In this study, we demonstrated that exposure to Cd caused remarkable pancreatic β-cell dysfunction and death, both in vitro and in vivo . Lipidomic analysis of Cd-exposed pancreatic β-cells using high-resolution mass spectrometry revealed that Cd exposure altered the profile and abundance of lipids. Cd exposure induced intracellular lipid accumulation, promoted lipid biogenesis, elevated pro-inflammatory lipid contents and inhibited lipid degradation. Furthermore, Cd exposure upregulated the expression levels of TNF-α, IL-1β and IL-6 in pancreatic β-cells and elevated the TNF-α, IL1-β and IL-6 levels in the serum and pancreas. Taken together, the results of our study demonstrated that environmental relevant Cd exposure causes pro-inflammatory lipids elevation and insulin secretion dysfunction in β-cells and hence exaggerates diabetes development. Combined exposure to environmental hazardous chemicals might markedly increase the probability of developing diabetes in humans. This study provides new metabolic and pharmacological targets for antagonizing Cd toxicity.